Postnatal neurogenesis and dopamine alterations in early psychosis - Inta, Dragos; Lima Ojeda, Juan Manuel Valentino; Gass, Peter (Recent patents on CNS drug discovery, 2012)
Schizophrenia is most likely a neurodevelopmental disorder with a characteristic delayed onset of symptoms occurring usually during transition from adolesc...